2021
DOI: 10.21511/ppm.19(2).2021.41
|View full text |Cite
|
Sign up to set email alerts
|

Transformational behaviors: Increasing work engagement in multinational environments

Abstract: The role of a leader is fundamental to increase organizational culture and facilitate employee engagement. However, organizations are not providing clear guidance on how to do it. This study aims to determine the relationship between leadership styles and employee engagement as well as to understand whether there is a correlation between an engaged employee and extra effort. The study uses a Multi-Leadership Questionnaire (MLQ-5x Rater Form) to measure employee perception of the leader styles and Utrecht Work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…From this we can conclude that the second hypothesis was accepted, that Manager Coaching Skills have a positive and significant influence on Empowerment, meaning that changes in Manager Coaching Skills have a unidirectional effect on Empowerment changes or in other words if Manager Coaching Skills increase, there will be an increase in Empowerment and statistically has significant influence on employee of the company. These results support the research conducted by [3]; [15].…”
Section: The Influence Of Manager Coaching Skills On Empowermentsupporting
confidence: 91%
See 1 more Smart Citation
“…From this we can conclude that the second hypothesis was accepted, that Manager Coaching Skills have a positive and significant influence on Empowerment, meaning that changes in Manager Coaching Skills have a unidirectional effect on Empowerment changes or in other words if Manager Coaching Skills increase, there will be an increase in Empowerment and statistically has significant influence on employee of the company. These results support the research conducted by [3]; [15].…”
Section: The Influence Of Manager Coaching Skills On Empowermentsupporting
confidence: 91%
“…H2. Manager coaching skills have a significant effect on empowerment [3]; [15].  Managers' coaching skills for work engagement.…”
Section: Hypothesis Of Researchmentioning
confidence: 99%
“…The fourth factorintellectual stimulation -describes a leader who has the skills to advocate intelligence and encourage problem solving mentality, and, finally, the fifth factor -individualized consideration -characterizes a leader who has the ability to recognize and promote individuality among teams. A recent study demonstrated that applying transformational behaviors can boost positively work engagement and organization outcomes in multinational environments (Valldeneu et al, 2021). However, there are no data yet on what kind of transformational leadership behavior is responsible for keeping satisfaction high among millennials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, passive-avoidant leadership is characterised by the total absence of leadership. According to previous studies ( Valldeneu et al, 2021 ) leadership style is closely related to organizational results, innovation, success and recognition of the company. Specifically, it has been seen that leaders who tend to adopt a more transformational leadership approach and avoid passive-avoidance attributes could improve organizational outcomes and work engagement of employees ( Valldeneu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…According to previous studies ( Valldeneu et al, 2021 ) leadership style is closely related to organizational results, innovation, success and recognition of the company. Specifically, it has been seen that leaders who tend to adopt a more transformational leadership approach and avoid passive-avoidance attributes could improve organizational outcomes and work engagement of employees ( Valldeneu et al, 2021 ). Bearing in mind these data, it seems important to know before hiring the candidate his degree or level of connection with each of the leadership styles.…”
Section: Introductionmentioning
confidence: 98%